DIPLOMASI KEBUDAYAAN JEPANG TERHADAP INDONESIA DALAM MENGEMBANGKAN BAHASA JEPANG - Nuraini "; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to describe a general overview of diplomatic relations between Indonesia and Japan, provide a description of the Japan Foundation in Indonesia, and explained . How the Japan Foundation made in the development of Japanese Japan through the Japan Foundation.The theory used in this research is cultural diplomacy theory,that is explained how the Japan Foundation using language as an instrument for cultural diplomacy to achive its goal,using intentional approaches to resource allocation, state and nation analysis, and this research method is a descriptive analytical method.The success of Japanese diplomacy culture in Indonesia can be seen from community reaction that want to know Japanese culture further and Japanese enthusiasts are on the rise, securing the positive role for Indonesia, but on the other hand can not deny the existence of obstacles in The language of Japanese language learning, such as lack of materials and equipment, information and teaching materials.Keywords: Image, cultural diplomacy, The Japan Foundation